DNA finger printing of S. Mutans present in the saliva of caries active children and those associated with intellectual disability – An RAPD analysis - A.R. Prabhakar; Gudla Sreeja; Saraswatthi V. Naik (Saudi Dental Journal)
Aim: The aim of this study is, to evaluate and compare the diversity of S. Mutans genotypes with respect to caries activity among normal children and intellectually disabled children, which would enable the clinician to plan better strategies for early caries detection, management and prevention. Materials and methods: Genotyping of S. Mutans was done by collecting the saliva samples from 40 caries active children (20 normal and 20 children associated with intellectual disability by Rapid amplified polymorphic DNA analysis using three arbitrarily primers (P1, P2, P3). Rapid amplified polymorphic DNA (RAPD) is preferred because of its reliability, reproducibility in generating genetic fingerprints of Streptococcus isolates. Results: Number of bacterial counts in Group I showed a mean of 111.6500 followed by the Group II with a mean of 102.6500. Therefore, the difference in the number of bacterial counts was not significant between the two groups (p < 0.001). Genotype encoding Primer 1 was present in almost 82.5% of the total population of both groups. Genotype encoding Primer 2 was present in 95% of the total population. Whereas, Genotype encoding Primer 3 was present in 20% of children associated with intellectual disability and 95% of normal children. Interpretation and conclusion: There was no significant difference in S. Mutans count of normal caries active children to that of caries active children with intellectual disability, but, there was a significance difference in the distribution of S. Mutans genotypes in both the groups. Keywords: Dental caries, S. Mutans, Genotypic diversity, Intellectual disability, RAPD analysis, DNA finger printing